(untitled) (Bangladesh Journal of Medical Microbiology, 2011)
Clinically diagnosed bronchial asthma patients comprising of new cases, on therapy or follow up were enrolled for this study to see if the new biological marker Eosinophilic cationic protein (ECP) can be used as a more precise marker to monitor therapy than the presently used conventional ones like FEV1% predicted, PEFR, and Circulating eosinophil (C.E) count. Out of 70 bronchial asthma patients, 30 intermittent, 4 mild persistent, 24 moderate persistent and 12 severe persistent asthma patients were included, while 45 cases were enrolled for follow up. Serum level of eosinophil granular protein, Eosinophilic cationic protein (ECP) was measured in relation to changes in their forced expiratory volume in 1st second (FEV1% predicted) and Circulating Eosinophil count (%) before and after therapy in 45 follow up patients on asthma therapy. In this study, it was observed that C.E count (%) and FEV1% predicted were not decreased significantly and serum eosinophilic cationic protein (ECP) decreased significantly (p<0.001) after asthma therapy. Thus, serum ECP level can be used as a biological marker than other conventionally used marker (FEV1, C.E count) to monitor therapeutic efficacy in bronchial asthma patients. DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15813 Bangladesh J Med Microbiol 2011; 05 (01): 3-7